¿Optimization or change of government? Radical populism’s foundational tendencies against a democratic institutionalism - Peruzzotti, Enrique (2018)
Since the consolidation of democratic governments in Latin America during these last decades, the debate sustained from political theory about the type of government needed for the region had been basically foreclosed. The discussions held circled around how to best optimize democracy (whether it be delegative or derivative) and its institutionalism. Nevertheless, the eruption of a new populism gave a new turn on this academic concern. With its proposal of a radical democracy, the new Latin- American populism defied what had become a common sense for it: that liberal democracy was the only viable change of government for the region. In this article, we try to critically appreciate both paths, and propose a third one where their contributions are reconciled and their limitations amended.